2021
DOI: 10.1186/s13028-021-00581-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of antimicrobial treatment on mortality associated with urinary tract disease in mink kits (Neovison vison)

Abstract: Mink urinary tract disease (MUTD) often presents as urolithiasis and/or cystitis and is known as an important cause of mortality in mink kits during the early growth season. Antimicrobial flock treatment has been routinely applied as preventive/therapeutic protocol on Danish mink farms with increased mortality associated with MUTD. The therapeutic effect of this treatment strategy has not previously been investigated. In this study, we applied controlled parallel group treatment trials to assess the effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Another disease that occurs in mink in the early stages of the growth of young animals is bacterial cystitis and urolithiasis [Mundbjerg et al 2020]. Mundbjerg et al [2021] report that bacterial cystitis is a serious problem on Danish farms, and the daily mortality of young mink in June and July may range from 0.3 to 0.7%. Mundbjerg et al [2020] found that cystitis and/or urolithiasis were associated with the fall of 33% of mink kits in 2015 and 2017.…”
Section: Nutritionmentioning
confidence: 99%
“…Another disease that occurs in mink in the early stages of the growth of young animals is bacterial cystitis and urolithiasis [Mundbjerg et al 2020]. Mundbjerg et al [2021] report that bacterial cystitis is a serious problem on Danish farms, and the daily mortality of young mink in June and July may range from 0.3 to 0.7%. Mundbjerg et al [2020] found that cystitis and/or urolithiasis were associated with the fall of 33% of mink kits in 2015 and 2017.…”
Section: Nutritionmentioning
confidence: 99%